Transition-Metal-Catalyzed Alkenyl sp2 C–H Activation: A Short Account - Maraswami, Manikantha; Loh, Teck-Peng (Synthesis, 2019)
Alkenes are ubiquitous in Nature and their functionalization continues to attract attention from the scientific community. On the other hand, activation of alkenyl sp2 C–H bonds is challenging due to their chemical properties. In this short account, we elucidate, discuss and describe the utilization of transition-metal catalysts in alkene activation and provide useful strategies to synthesize organic building blocks in an efficient and sustainable manner.1 Introduction2 Breakthrough3 Controlling E/Z, Z/E Selectivity3.1 Esters and Amides as Directing Groups3.2 The Chelation versus Non-Chelation Concept4 Other Alkene Derivatives5 Intramolecular C–H Activation6 Conclusion and Future Projects
Keywords: transition metals; enamides; acrylamides; macrocycles; acrylates; alkenylation; alkynylation